Modeling of relay protection of electric power system using Matlab/Simulink - Vo Tien, Dung; Thai Huu, Nguyen; Tran Duy, Trinh (Vietnam Journal of Science and Technology, 2024)
The criteria for evaluating protective relaying devices encompass verifying both their design and application performance. Utilizing modeling and simulation techniques enables cost-effective completion of substantial design, evaluation, and testing tasks for physical relays and power systems. To effectively design, set, test, and evaluate protective relays, one requires software tools proficient in modeling both the protective relays of various designs as well as the surrounding power system. In this article, the authors present new models of protection that allow to simulate the overcurrent relay (51), instantaneous overcurrent relay (50) and differential relay (87) by using Matlab/Simulink. Initially, a methodology that presents how to build a library, including the different models and their communication architectures. Secondly, a case study in 220 kV transmission systems is selected as an example for fault simulation and relay testing for each relay model and the coordination protection. The simulation results are given and a description of how this case study can be used to compare protection schemes. In particular, the new contribution of this article is that the overcurrent relay is built based on a mathematical model according to IEC 60255 and IEEE C37.112-1996 standards. The results have shown that the difference between the proposed model and theoretical calculations is very small.